2021
DOI: 10.3389/fsurg.2021.671301
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. Open Repair Surgery for the Treatment of Communicating Hydrocele in Children: A Retrospective Study From a Single Center

Abstract: Purpose: This study evaluated the outcomes of laparoscopic repair (LR) and open repair (OR) surgery for communicating hydrocele in children.Patients and Methods: We collected the clinical data and follow-up data of all boys (<14 years) who underwent communicating hydrocele surgery in the pediatric surgery department at Yijishan Hospital of Wannan Medical College from January 2017 to December 2018 and retrospectively analyzed the data.Results: In this study, 155 patients were retrospectively enrolled, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the study by Elhaddad et al, there was also no evidence of recurrent hydrocele or testicular atrophy in any of the cases [5]. However, the study by Liu et al showed a significantly higher recurrence rate in the OR group than in the LR group (6.67% vs. 0%, p = 0.034) [13]. In the study by Zhang et al, 9 recurrences (1.1%) occurred in the 950 laparoscopic procedures, which did not differ significantly from the 5 cases in the open repair group (1.3%) [8].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the study by Elhaddad et al, there was also no evidence of recurrent hydrocele or testicular atrophy in any of the cases [5]. However, the study by Liu et al showed a significantly higher recurrence rate in the OR group than in the LR group (6.67% vs. 0%, p = 0.034) [13]. In the study by Zhang et al, 9 recurrences (1.1%) occurred in the 950 laparoscopic procedures, which did not differ significantly from the 5 cases in the open repair group (1.3%) [8].…”
Section: Discussionmentioning
confidence: 87%
“…All postoperative complications were treated conservatively. However, the study by Liu et al showed a significantly higher persistence of scrotal swelling in the OR group than in the LR group (10% vs. 1.54%, p = 0.034) [13]. Zhang et al also reported a significantly higher incidence of scrotal edema in the OR group than in the LR group (71 (18.6%) vs. 0, p < 0.01).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This collection can be regressed or persistent. [17][18][19][20] Figure 6. A 27-year-old male patient presents with swelling of the bilateral scrotum and left lower abdomen, accompanied by persistent dull pain.…”
Section: Managementmentioning
confidence: 99%
“…Note that if the processus vaginalis is not ligation, it can lead to postoperative fluid collection (Figure 9). This collection can be regressed or persistent 17–20 …”
Section: Managementmentioning
confidence: 99%